2017
DOI: 10.1080/1059924x.2017.1319315
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate and Paraquat in Maternal and Fetal Serums in Thai Women

Abstract: These results show that pregnant women who work in agriculture or live in families that work in agriculture have higher exposures to the herbicides glyphosate and paraquat. The potential for long-term health impacts of these prenatal exposures to children should be evaluated, and greater regulation of the sale and use of herbicides should be considered in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 19 publications
3
39
1
Order By: Relevance
“…One such study focused on 82 Thai women during their seventh month of pregnancy. Kongtip et al [42] reported the number of women falling within progressively higher levels of glyphosate in maternal serum and umbilical cord blood. Levels varied by some 100-to 200-fold, as evident in Fig.…”
Section: More Data Needed On the Distribution Of Exposure Levelsmentioning
confidence: 99%
“…One such study focused on 82 Thai women during their seventh month of pregnancy. Kongtip et al [42] reported the number of women falling within progressively higher levels of glyphosate in maternal serum and umbilical cord blood. Levels varied by some 100-to 200-fold, as evident in Fig.…”
Section: More Data Needed On the Distribution Of Exposure Levelsmentioning
confidence: 99%
“…We identified 1,908 records and included 19 studies in our final qualitative analysis ( Figure 1). Seventeen studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] were peer-reviewed and two were preprints [27,28]. Quality appraisal is included in Tables 1, S2 and S3.…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…CC-BY 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity. (which was not certified by peer review) preprint and/or PLWH without COVID-19, [11,12,14,15,23,25,26], two studies compared only to a HIV-negative cohort [13,19], two studies compared only cohorts of PLWH with and without COVID-19 [17,22] and three studies compared only the characteristics of PLWH with different COVID-19 disease severity [20,21,24].…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, glyphosate and its major metabolite, aminomethylphosphonic acid (AMPA), have been detected in surface water, sediments and soil that surround horticultural production areas of different regions of Argentina (Aparicio et al, 2013;Bonansea et al, 2017;Lupi et al, 2015;Mac Loughlin et al, 2017;Primost et al, 2017;Ronco et al, 2016). These pesticide residues have also been detected in foodstuff (EFSA, 2017) and human urine (Connolly et al, 2017;Goen et al, 2017;Mills et al, 2017;Parvez et al, 2018) and serum samples (Kongtip et al, 2017).…”
Section: Introductionmentioning
confidence: 99%